Analisis Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Etos Kerja Guru - Eko Arif Susanto (Studia Manageria, 2022)
This research is qualitative research. The subject of this research is the head of the Madrasah. The data collection techniques used were interviews, observation, and documentation. Using interactive data analysis techniques Miles and Huberman. The data validity test used the source triangulation technique. Based on the results of the study, it shows that the role of the head of the madrasah in improving the work ethic of teachers is very good, namely acting as a formal official, as a manager, as a leader, as an educator, as an administrator, as a madrasah as a supervisor, as an innovator, as a motivator. In addition, there are supporting and inhibiting factors. The supporting factors are (1) the availability of adequate facilities and infrastructure, (2) good teacher discipline, (3) the qualifications of teacher education that are relevant to the subject being managed, (4) communication between teachers and staff is maintained, while the inhibiting factors are (1) there are still teachers who continue to use the ancient learning model, (2) late disbursement of BOS funds as the main source of madrasah funding, (3) difficulty in the process of applying for teacher certification through the Education Information and Management System and Education Personnel of the Ministry of Religion"SIMPATIKA" application, (4) diverse teacher personnel, so difficult to understand one by one. Based on the role of the head of the madrasah, it shows that the work ethic of the teachers at Madrasah Tsanawiyah Subulussalam 2 is very high. Thus it can be concluded that the leadership role of the principal is very important in improving the work ethic of teachers.